2015
DOI: 10.3109/02713683.2015.1038359
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Culture System to Induce Neurite Outgrowth From Retinal Ganglion Cells in Three-Dimensional Retinal Aggregates Differentiated From Mouse and Human Embryonic Stem Cells

Abstract: We successfully optimized the culture conditions to enhance lengthy and high-frequency neurite outgrowth in mouse and human models. The procedure would be useful for not only developmental studies of RGCs, including maintenance and projection, but also clinical, pathological, and pharmacological studies of human RGC diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…Although there are several reports on the function and neurite outgrowth of human iPSC-RGCs differentiated by an organotypic culture system, 25,30,31 little has been reported on purified RGCs from 3D retinal organoids. 24 It is difficult to identify RGCs induced by direct genomic reprogramming completely as they are restricted to the eye.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are several reports on the function and neurite outgrowth of human iPSC-RGCs differentiated by an organotypic culture system, 25,30,31 little has been reported on purified RGCs from 3D retinal organoids. 24 It is difficult to identify RGCs induced by direct genomic reprogramming completely as they are restricted to the eye.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported an explant culture procedure in which human ESC-derived retinal organoids exhibit significant neurite outgrowth. 25 Following this trend, we applied an immunopanning method designed for both rodent and human systems. We applied this to mouse retinas and mouse ESC-derived retinal organoids and compared the morphologic and immunohistochemical features of the purified cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En route to differentiating photoreceptors and other later-born retinal cells, differentiation of RGC-like cells has been reported, 43,44 but only a few protocols have focused on RGC differentiation. 4547 …”
Section: Pluripotent Stem Cells As a Source Of Rgcsmentioning
confidence: 99%
“…In a 3D self-organization technique, intrinsic cellular programs drive self-organization of stem cells to form an optic cup, which can further differentiate into a multilayered structure containing various retinal cells. 48,49 By optimizing the 3D culture technique, Maekawa et al 47 reported successful RGC neurite outgrowth from the 3D optic vesicles.…”
Section: Pluripotent Stem Cells As a Source Of Rgcsmentioning
confidence: 99%